Equality of Gender Rationality in the Novel Aku Lupa Bahwa Aku Perempuan by Ihsan Abdul Quddus - Sri Lestari; Alif Nur Khayati; Fllorenta Fani Diah Aprilia Putri (UIN Raden Mas Said Surakarta, 2022)
Knowledge about gender should focus more on various circles. In this study, it aims to describe the rational form of equality of gander in the novel Aku Lupa Bahwa Aku Perempuan by Ihsan Abdul Quddus. This research uses a qualitative descriptive method by analyzing the novel. Data were obtained from various sources, including a related novel titled Aku Lupa Bahwa Aku Perempuan by Ihsan Abdul Quddus. The results of this study show that of all the existing gender equality, the most appropriate equality is to know the characteristics of each gender itself. Various roles in life are already supposed to be studied and applied in life, in accordance with the social constructions taking place and pay attention to the social, political, economic, cultural and other spheres. However, in reality, there are many cases of gender equality that are still the same as in the novel. There is no awareness of their respective roles, especially in terms of households.